Religious and Nationalist Character Formation Through School Culture - Aziz, Muhammad; Sholikah, Sholikah (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2026)
his study examines how religious and nationalist character formation is cultivated through school culture at SMP Mamba’us Sholihin Tuban, an Islamic junior high school in Indonesia. Moving beyond program-based character education, this research conceptualizes character formation as a sustained cultural process embedded in daily school practices, norms, symbols, and leadership models. Using a qualitative approach and case study, the data for this study were collected from the Principal, Vice Principal, Teachers, and Students of SMP Mambaus Sholihin Tuban, through in-depth interviews, document analysis, and observations of school activities. Data were processed using content analysis, presentation, and conclusion drawing, supported by triangulation of sources and techniques to ensure credibility. Interviews were conducted with school leaders and administrators, teachers, and students, and observations were conducted. Data were analyzed using qualitative methods validated through triangulation of sources and techniques, then interpreted based on selected theories. The findings reveal that religious and nationalist values are not treated as separate domains but are integrated within a cohesive school culture shaped by routine religious practices, civic rituals, teacher role modeling, and institutional regulations. This integration fosters students’ spiritual discipline, moral responsibility, and national commitment simultaneously. The study confirms the relevance of Character Education Theory and School Culture Theory in the Indonesian Islamic education context while demonstrating how local religious traditions and national identity discourses interact constructively. The research contributes to the growing discourse on religious–nationalist character formation by offering an empirically grounded model of culturally embedded character education that may inform policy and practice in Islamic schooling contexts.